1977
DOI: 10.1002/bit.260190508
|View full text |Cite
|
Sign up to set email alerts
|

Assimilation of liquid hydrocarbon by microorganisms. II. Growth kinetics

Abstract: The growth kinetics of a microorganism with high affinity for liquid hydrocarbon which has a low solubility in water was investigated for Candida intermedia IFO 0761 in our previous work. The microorganism contained a hydrocarbon pool in and/or on the cell. The transfer of water-soluble substrates to the cell was not the rate-limiting step in the growth of C. intermedia accompanied by clump formation with liquid hydrocarbon. The operating conditions necessary for the oxygen supply for the growth were adequate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1978
1978
2007
2007

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…A possible explanation could be the formation of a biofilm on hydrocarbon. Indeed, this phenomenon was observed in the laboratory for yeast or bacteria growing on n-alkanes (Blanch & Einsele, 1973;Bouchez-Naïtali et al, 2001;Mallee & Blanch, 1977;Miura et al, 1977). These authors showed that when microorganisms had a strong affinity to oil, they attached themselves on hydrocarbon (direct interfacial uptake) and formed flocs consisting of a conglomeration of cells, hydrocarbon droplets and air bubbles.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…A possible explanation could be the formation of a biofilm on hydrocarbon. Indeed, this phenomenon was observed in the laboratory for yeast or bacteria growing on n-alkanes (Blanch & Einsele, 1973;Bouchez-Naïtali et al, 2001;Mallee & Blanch, 1977;Miura et al, 1977). These authors showed that when microorganisms had a strong affinity to oil, they attached themselves on hydrocarbon (direct interfacial uptake) and formed flocs consisting of a conglomeration of cells, hydrocarbon droplets and air bubbles.…”
Section: Introductionmentioning
confidence: 85%
“…A linear growth phase was observed with a rate of 1.8 mg.h -1 . This linear phase was observed with almost microorganisms growing on n-alkane (Blanch & Einsele, 1973;Bouchez-Naïtali et al, 2001;Chakravarty et al, 1975;Joannis, 1998;Mallee & Blanch, 1977;Miura et al, 1977) whatever the mechanism of uptake (interfacial accession or biosurfactant-mediated hydrocarbon uptake). For interfacial uptake, growth was exponential until the interfacial area was covered with cells, then the onset of the linear phase occurred.…”
Section: Biofilm Growth Kineticsmentioning
confidence: 98%
“…They showed that for C. intermedia, which adsorbed strongly to the oil droplets, the uptake rate of drop-form hydrocarbon was nearly equal to that of accommodated hydrocarbon. For C. tropicalis, which did not adsorb as strongly to oil droplets, Miura et al 24,25 found that the uptake rate of drop-form hydrocarbon was lower than that of accommodation-form hydrocarbon. They also showed that the uptake rate was very small for dissolved hydrocarbons.…”
Section: Introductionmentioning
confidence: 99%